2019
DOI: 10.1177/2158244019829564
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Evaluation Practices and Academic Staff Motivation: Implications in Higher Education Within Rwandan Context

Abstract: This study sought to determine the relationship between monitoring and evaluation (M&E) practices and academic staff motivation in higher education, from a Rwandan perspective. Particularly, the study aimed at describing the M&E practices applied, assessed how quality of feedback affects academic staff motivation, and determined the relationship between M&E practices and academic staff motivation. The study employed a mixed-methods approach to collect data from academic staff. A total of 105 faculties were sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…This study goes in line with our literature review findings and contributes to the study of the problem of introducing monitoring in the educational process in primary school. First, the study broadened previous studies dedicated to motivation of pupils and increasing their learning engagement (through improving teaching skills and, accordingly, optimizing teaching and learning) (Niyivuga, Otara & Tuyishime, 2019). Second, it enhanced the ways of continuous improving education quality (O'Mahony & Garavan, 2012)?…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study goes in line with our literature review findings and contributes to the study of the problem of introducing monitoring in the educational process in primary school. First, the study broadened previous studies dedicated to motivation of pupils and increasing their learning engagement (through improving teaching skills and, accordingly, optimizing teaching and learning) (Niyivuga, Otara & Tuyishime, 2019). Second, it enhanced the ways of continuous improving education quality (O'Mahony & Garavan, 2012)?…”
Section: Discussionmentioning
confidence: 94%
“…Second, it enhanced the ways of continuous improving education quality (O'Mahony & Garavan, 2012)? and the ways to motivate teaching staff (Shah & Nair, 2012;Duan, Du & Yu, 2018;Niyivuga, Otara & Tuyishime, 2019). Third, this study tested the framework and principles for monitoring primary school education process and addressed the aspects of its effectiveness (Hoover, 2009;Kayani, et al, 2011;Mngomezulu, 2015;Ferdaus, 2016;Fulton, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the study results, Mpisane (2015) found out that HODs of Science were involved in holding meetings assists in empowering teachers as they share information and improve their communication skills and enhance their knowledge. In addition, Niyivuga et al (2019) also found out that HODs of Science in Rwanda schools organised departmental meetings to discuss shortfalls and achievement. Therefore, the result suggests that subject meetings do not happen regularly considering some schools do not teach all the three science subjects at once while others have inadequate number of teachers teaching specific science subjects.…”
Section: Influence Of Monitoring and Control Skills By Hods Of Science And Academic Performance Of Students In Science Subjectsmentioning
confidence: 99%
“…It has been influenced by various aspects including globalization, dynamic environments, workforce diversities, and technological transformations [18]. Furthermore, many studies suggested that there is no one-fits-all approach to the assessment of performance of human resources development, but the monitoring and evaluation is an important tool, which can be used to guide human resources to enhance performance in higher education [19,20]. Moreover, numerous studies support the idea that monitoring and evaluation had a significant impact on academic motivation [21]; organizational effectiveness [22]; and academic performance [23].…”
Section: Introductionmentioning
confidence: 99%